How Rare Are TESS Free-floating Planets? - Yang, Hongjing; Zang, Weicheng; Gan, Tianjun; Kuang, Renkun; Gould, Andrew; Mao, Shude (Astrophysical journal. Letters, 2024)
Recently, Kunimoto et al. claimed that a short-lived signal in the Transiting Exoplanet Survey Satellite (TESS) Sector 61 database was possibly caused by a microlensing event with a terrestrial-mass free-floating planet (FFP) lens. In this study, we investigate TESS’s ability to detect microlensing FFPs by considering the detailed source information (e.g., distance and radius), the TESS photometric accuracy, and finite-source effects. Using the FFP mass function from microlensing surveys toward the Galactic bulge, we find that only 0.0018 microlensing events are expected to be detected in TESS Sector 61 for the entire planetary mass range. The reported signal is unlikely to be a real microlensing event, which is consistent with the evidence from the long-term Optical Gravitational Lensing Experiment data that the signal was likely due to a stellar flare. By extrapolating our result to fainter stars until T = 16 mag and adopting a possible optimized search algorithm, we find that only ∼1 FFP event can be detected in the entire TESS mission within the first 7 yr. Significant improvements in our understanding of FFPs still require future satellite missions, such as Roman and Earth 2.0, which can detect thousands of FFPs.